Profiles of Childhood Maltreatment: Associations with Sexual Risk Behavior during Adolescence in a Sample of Racial/Ethnic Minority Girls. Issue 4 (14th January 2021) - Niu, Li; Brown, Joshua; Till Hoyt, Lindsay; Salandy, Anthony; Nucci‐Sack, Anne; Shankar, Viswanathan; Burk, Robert D.; Schlecht, Nicolas F.; Diaz, Angela
Abstract : This study examines associations between childhood maltreatment and developmental trajectories of sexual risk behaviors (SRBs) in a sample of 882 sexually active adolescent girls, predominantly Hispanic or Black, assessed every 6 months between 13 and 23 years. Latent profile analyses revealed four distinct maltreatment profiles: Low Maltreatment (76%), Moderate Emotional Neglect Only (15%), Severe Physical/Emotional Abuse (3%), and Severe Sexual Abuse (6%). Multilevel growth analyses showed the Moderate Emotional Neglect Only and Severe Sexual Abuse profiles exhibited more SRBs starting in late adolescence, and the Severe Sexual Abuse profile also exhibited a faster increase than the Low Maltreatment profile. Understanding heterogeneity within maltreated populations may have important implications for healthy sexual development.